Encapsulamento do extrato de erva-mate (Ilex paraguariensis) tostada por spray drying utilizando maltodextrina e β-glucana como material de parede - Zanoelo, Maiara (2022)
Roasted mate tea is rich in compounds with antioxidant activity, such as phenolic acids, flavonoids and alkaloids, especially caffeine, caffeic, chlorogenic and ferulic acids, rutin and quercetin. It is produced from the roasting of yerba-mate leaves (Ilex paraguariensis), after the steps of roasting, drying and milling. In these stages, contaminant substances are formed, such as polycyclic aromatic hydrocarbons (PAHs), which enter in contact with the leaves through smoke. Seeking to offer an extract with better stability and lower content of undesired compounds, microencapsulation is a very promising strategy. Thus, in this work, roasted mate tea was microencapsulated using 15% of maltodextrin and different concentrations of lasiodiplodan (0.5, 0.875 and 1.25%), a microbial (1→6)--glucan as wall materials. The microcapsules were characterized for encapsulation efficiency, hygroscopicity, moisture, water activity, solubility in water, dissolubility, scanning electron microscopy (SEM), Fourier transforms infrared spectroscopy (FTIR), thermal analysis, colorimetry, antioxidant activity, (ABTS, FRAP, DPPH and CAOT), the content of phenolic compounds, phenolic compounds and caffeine by high-efficiency liquid chromatography and identification and quantification of PAHs by gas chromatography. The microencapsulated samples showed a yield between 44.92 and 56.39%, with encapsulation efficiency varying from 66.54 to 70.16%; the PAHs acenaphthylene (1,380 to 1,524 μg·g-1), acenaphthene (3,109 to 4,375 μg·g-1), fluorene (1,446 to 1,843 μg·g-1), chrysene (0.093 to 0.141 μg·g-1), and benzo[a]pyrene (0.988 to 1.493 μg·g-1) were identified and quantified. It was also possible to identify indeno(1,2,3-cd)pyrene ins the studied samples. The moisture of the microcapsules varied from 0.302 to 0.526%, the water activity from 0.083 to 0.154, the hygroscopicity from 21.37 to 23.413%, the solubility from 20.703 to 51.263 s and solubility varied from 95,734 to 98,570%. The microcapsules had shown spherical structures and irregular surfaces, with dimensions, ranging from 2.30 to 15.3 μm. Bands related to the presence of phenolic acids, flavonoids and polyphenolic compounds were identified by the FTIR technique. Colour varied among the samples from 1.079 to 3.979. Thermal analysis indicates that the encapsulates have a good thermal stability, with no degradation below 250 °C. For HPLC, 4-caffeoilquinic acid varied from 6.255 to 11.137 mg∙g-1; 7 caffeine varied from 5.004 to 8.873 mg∙g-1; caffeic acid varied from 2.041 to 3.596 mg∙g-1; rutin varied from 1.583 to 2.313 mg∙g-1; ferulic acid varied from 2.795 to 4.002 mg∙g-1. The content of total phenolic compounds varied from 73,065 to 74,155 mg EAG·g-1; ABTS varied from 0,869 to 1,006 μmol de TEAC·g-1; FRAP varied from 11640,514 to 14353,439 μmol FeSO4·g-1; DPPH varied from 0,411 to 0,437 μmol de TEAC·g-1; CAOT varied from 124,875 to 288,458 mg EAAS·g-1. Therefore, the results indicate that the microcapsules elaborated from roasted mate tea in these conditions may be a source of PAHs. Microencapsulation by spray dryer presented as a favorable process where maltodextrin is a low-cost protective agent, and allied with the properties of lasiodiplodan, can be a good option when used to stabilize extracts.